Efficiency of using tower cranes in the construction of multi-storey buildings - Dobrovolskyi, S. V.; Matvyevskyi, S. V. (Ways to Improve Construction Efficiency, 2020)
Among publications and studies on the exploitation of tower cranes and mechanization, the problem of their rational choice and a techno-economic analysis of the exploitation is not disclosed sufficiently. Based on a comprehensive study of tower cranes of Ukrainian and foreign production, a comparison of technical characteristics, market value of exploitation and established relationships between these parameters, recommendations were developed on the rational use of tower cranes depending on the construction conditions. The work uses empirical and theoretical research methods. The research materials were obtained by observation, measurement and unstructured interview (knowledge transfer interview). The obtained information and hypotheses of the authors were analyzed and formed in the graphic model. For the study, the KB-674 (676) and Liebherr 280 EC-H12 Litronic models were selected. According to the technical passport of the KB-674 (676) tower crane, the specifications did not have enough information for comparison with similar ones in the Liebherr 280 EC-H12. In this regard, the operations of the KB-674 crane located at the construction site of the residential complex "Odessa Boulevard", v. Novoselki were explored and studied. According to the results of the observation, the dependence of the hoist speed on the mass of the load was revealed. The cost of exploiting tower cranes directly depends on the time of their use and the conditions of their exploitation. The parameters of the tower crane, such as their height, “degree of novelty”, etc., are accepted the same for both models. Based on the data obtained, simplified formulas for calculating the cost of exploitation of KB-674 and Liebherr 280 EC-H 12 were compiled. Using the Microsoft Excel software package, we obtain the calculation results in tabular and graphical forms. As a result of our research, it was found that the use of tower cranes KB-674 (676) is advisable mainly for building large-panel type construction with a height of not more than 80 m and for the duration of work no more than 2.5 years. The KB-674 crane model needs further modernization of operational characteristics, because of the gradually growing in complexity of the purposes it was created for and demands of modern construction is growing.